V=(x)(x-6)(x-2)

Simple and best practice solution for V=(x)(x-6)(x-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for V=(x)(x-6)(x-2) equation:


Simplifying
V = (x)(x + -6)(x + -2)

Reorder the terms:
V = x(-6 + x)(x + -2)

Reorder the terms:
V = x(-6 + x)(-2 + x)

Multiply (-6 + x) * (-2 + x)
V = x(-6(-2 + x) + x(-2 + x))
V = x((-2 * -6 + x * -6) + x(-2 + x))
V = x((12 + -6x) + x(-2 + x))
V = x(12 + -6x + (-2 * x + x * x))
V = x(12 + -6x + (-2x + x2))

Combine like terms: -6x + -2x = -8x
V = x(12 + -8x + x2)
V = (12 * x + -8x * x + x2 * x)
V = (12x + -8x2 + x3)

Solving
V = 12x + -8x2 + x3

Solving for variable 'V'.

Move all terms containing V to the left, all other terms to the right.

Simplifying
V = 12x + -8x2 + x3

See similar equations:

| y^2-8y+2x-10=0 | | x-8/6=x+2/9 | | 0.0765t^2-0.884t+1.874=0 | | 5x=10x-35 | | x-0.3x=150 | | X^2-8y+2x-10=0 | | (y^1-y^2)=4(X^1-x^2) | | 3y-y=60 | | 0.0765t^2-0.884t+1.874t=0 | | L=a+(n-1) | | 180x=60 | | r-10=7 | | 3x+21=2x | | 1/2x=-13 | | y=6-2+6 | | -21x+3y=7 | | 50x=25 | | (2x^3y^-2/x^2y^5)^-2 | | 50x=26 | | 54k^2-54=0 | | 7(u+1)=4u-23 | | 4x-12000x^2=0 | | 0.11y+0.06(y+9000)=1900 | | x=108.8-27.2x+x^2 | | 8x+17=x+38 | | 4=-8w+5(w+5) | | 3x+16y+1z=93 | | 9b^2+18b-31=9 | | 1.2+x=0.3 | | 25-x/3=15.6 | | 9x^2+18b-31=9 | | 16/21x3/5x5/8= |

Equations solver categories